Digital Identity on Social Media: A Social Construction Of Technology Based Systematic Analysis - Agnes Yusuf (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Studies on digital identity on social media are extensive, but the specific problem remains that the literature is fragmented in explaining how identity construction is shaped simultaneously by user meaning-making and platform design. This study addresses that problem by systematically synthesizing prior findings through the Social Construction of Technology (SCOT) lens. Using a systematic literature review guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), 15 peer-reviewed articles published between 2016–2025 were selected and analyzed thematically. The results show three consistent patterns: (1) digital identity is constructed through ongoing negotiation between users and audiences under cultural norms; (2) platform affordances and governance (e.g., visibility mechanisms, interaction features, and moderation rules) constrain and enable identity performance; and (3) identity construction is recursive—users adapt to platform structures while their practices also stabilize or reshape how technologies are used and interpreted. These findings indicate that digital identity on social media is best understood as a socio-technical outcome produced by reciprocal interactions between social contexts and technological arrangements.